Sebaran Lengas Tanah Akibat Pembuatan Lorong Pengatus Dangkal pada Tanah Sawah - Siti Suharyatun; Bambang Purwantana; Abdul Rozaq; Muhjidin Mawardi (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2013)
Mole drainage is an alternative which can be used to increase the rate of soil moisture decrease in paddy soil at the end of the rainy season. By using mole drainage, the rate of soil moisture decrease goes up to a certain condition (from saturated to field capacity) which is suitable for early growth of crops. This study aimed at describing changes and distribution of soil moisture in paddy soil in which shallow mole drainage had been formed. Those changes and distribution were used to predict the rate of soil moisture decrease in paddy soil after mole drainage was formed. The study was conducted in the laboratory using a soil bin, a model of mole plough, and soils that was kept homogeneous in the boxes. The experiment was conducted in the Laboratory of Energy and Agricultural Engineering, Agricultural Engineering Department, Gadjah Mada University. The mole drainage was installed in three paddy soils with different clay content, namely 13.12% (A), 41.17% (B) and 53.36% (C). Soil moisture content was measured periodically by using gypsum blocks. The results showed that the three types of soils in which shallow mole drainage was formed had different characteristics of soil moisture changes. The formation of mole drainage in soil with low clay content (A) had no effect for the declining rate of soil moisture. On the contrary, the shallow mole drainage formed in the soil with higher contents of clay B and C influenced the rate of soil moisture decrease. High rate of soil moisture decrease in the soil B and C occurred at the beginning of the formation of mole drainage and went on up to the 3th hours of observation. Based on the distribution of soil moisture at different points at some distances from the center of mole drainage and the equation of the rate of soil moisture decrease found in the experiment, it could be inferred that moles formed in soils B and C could be used as mole drainage and the rate of soil moisture decrease in soil C was cumulatively higher than in soil B.ABSTRAKLorong pengatus merupakan salah satu alternatif guna mengatasi lamanya masa tunggu tanam palawija di lahan sawah pada akhir musim penghujan akibat kadar lengas tanah yang terlalu tinggi. Lorong pengatus dibuat untuk mempercepat laju penurunan kadar lengas sehingga sesuai untuk pertumbuhan awal tanaman palawija. Penelitian ini bertujuan mendeskripsikan perubahan dan sebaran lengas tanah yang terjadi akibat pembentukan lorong pengatus dangkal, untuk digunakan sebagai salah satu dasar memperhitungkan laju penurunan kadar lengas yang terjadi pada tanah sawah yang dibuat lorong pengatus. Penelitian dilakukan dalam skala laboratorium dengan menggunakan soil bin, model bajak lorong, dan tanah di dalam boks yang dijaga homogenitasnya. Penelitian dilaksanakan di Laboratorium Energi dan Mesin Pertanian, Jurusan Teknik Pertanian, FTP-UGM. Lorong pengatus dibuat pada 3 jenis tanah sawah dengan kadar lempung yang berbeda, yaitu 13,12% (tanah A), 41,17% (tanah B) dan 53,36% (tanah C). Pengukuran kadar lengas tanah dilakukan secara periodik menggunakan gypsum blok. Hasil penelitian menunjukkan bahwa ketiga jenis tanah yang dibuat lorong pengatus mempunyai karakteristik perubahan lengas tanah yang berbeda, Pembentukan lorong pengatus pada tanah dengan kadar lempung rendah (tanah A) tidak memberikan pengaruh terhadap laju penurunan lengas tanah, tetapi pada tanah dengan kadar lempung tinggi (tanah B dan C) berpengaruh terhadap laju penurunan lengas tanah. Laju penurunan lengas tanah kumulatif yang tinggi terjadi pada awal pembentukan lorong sampai 30 jam pasca pembentukan lorong. Dari distribusi lengas tanah pada jarak yang berbeda dari pusat lorong dan dari persamaan laju penurunan lengas hasil eksperimen, lorong yang dibuat pada tanah B dan C dapat berfungsi sebagai lorong pengatus. Peningkatan laju penurunan lengas tanah kumulatif tanah C lebih besar dibanding tanah B.